Analysis of Quality of Work Life and Performance of Midwives in Lamongan in 2025 - Supratikto Supratikto; Sri Utami Ady; Nur Sayidah (International Forum of Researchers and Lecturers, 2025)
The Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are critical indicators in assessing the quality of public health services. In 2024, both MMR and IMR in Lamongan Regency remained relatively high, indicating the need for strengthened health interventions. Health workers, especially midwives, play a vital role in improving maternal and child health. One of the government’s strategies to reduce maternal and infant mortality is expanding midwife service coverage at primary health facilities and ensuring the presence of village midwives as the frontline providers across the region. Village midwives are expected to meet established service standards to ensure the quality of maternal and child health care. Service effectiveness and efficiency are commonly measured through indicators such as first antenatal visit coverage (K1), fourth antenatal visit coverage (K4), postpartum visit coverage (KF3), and delivery assistance by health workers. However, in Lamongan Regency, the performance of village midwives has not been optimal, with several indicators falling short of set performance targets.This study aimed to analyze the relationship between the quality of work life and the performance of village midwives in Lamongan Regency in 2025. The research used a quantitative method with a cross-sectional study design. The study population comprised all village midwives in Lamongan Regency, with a sample of 80 respondents selected randomly. The independent variable in this study was the quality of work life, while the dependent variable was village midwife performance. Data were collected through questionnaires and analyzed using the chi-square statistical test. The results showed no significant relationship between the quality of work life and the performance of village midwives in Lamongan Regency in 2025. These findings suggest that other factors beyond work life quality may influence midwives’ performance.